Acantosis nigricans y su asociación con insulinorresistencia en población infantil menor a 15 años con sobrepeso u obesidad - Madrigal, Diana (2017)
Context: acanthosis nigricans in adult subjects with obesity is a cutaneous marker of insulin resistance.Objective: to determine the association between acanthosis nigricans and insulin resistance in pediatric patients. ubjects and methods: a case control study that evaluated children and adolescents between 6 and 15 years of age who attended the outpatient clinic of Dermatology of the Baca Ortiz Pediatric Hospital of Quito, from July to September 2015, were studied. Patients were recruited by non-probabilistic sampling, conforming two groups: cases and controls, with 25 subjects each.Results: it was determined in 15 patients (60%) with acanthosis nigricans presented insulin resistance; Of these, 6 patients (24%) and 19 patients (76%) were classified as moderate acanthosis nigricans, being more predictive of insulin resistance in subjects with obesity (p = 0.001). Patients with severe obesity and acanthosis nigricans had an OR of 54 (2.85-99.32) while patients diagnosed with obesity and moderate acanthosis nigricans had an OR of 12 (1.29-86.20).Conclusion: moderate and severe acanthosis nigricans in children and adolescents with obesity constitutes a cutaneous sign of insulin resistance